2018
DOI: 10.3892/or.2018.6737
|View full text |Cite
|
Sign up to set email alerts
|

JIB‑04 induces cell apoptosis via activation of the p53/Bcl‑2/caspase pathway in MHCC97H and HepG2 cells

Abstract: JIB-04 is a structurally unique small molecule, known to exhibit anticancer activity and to inhibit the growth of human lung cancer and prostate cancer cell lines. However, the anticancer effect of JIB-04 against human hepatic carcinoma, and its underlying mechanisms, are still unclear. In the present study, MHCC97H and HepG2 cells were employed to investigate the anticancer effects of JIB-04 on cell viability and apoptosis. Annexin V/PI staining, a CCK-8 assay and western blot analysis demonstrated that JIB-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The upregulation of TP53 expression that is induced by rAd-p53 treatment promoted human cervical cancer cell apoptosis through activation of the Bax gene and suppression of the Bcl-x gene and resulted in cell cycle arrest at the G 2 /M phase ( 40 ). The results of the present study are consistent with those observed in previous reports, which have demonstrated that TP53 activation is associated with liver cancer cell apoptosis by regulating the expression of Bcl-2 and caspases ( 41 , 42 ), in addition to inhibiting cancer cell migration ( 43-45 ). TP53 activation has also been previously reported to serve an inhibitory role in the EMT process, in human oral mucosal fibroblasts and oral submucous fibrosis by downregulating N-cadherin expression ( 46 ) and in colorectal cancer cells by downregulating Snail expression ( 37 ), which are findings consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The upregulation of TP53 expression that is induced by rAd-p53 treatment promoted human cervical cancer cell apoptosis through activation of the Bax gene and suppression of the Bcl-x gene and resulted in cell cycle arrest at the G 2 /M phase ( 40 ). The results of the present study are consistent with those observed in previous reports, which have demonstrated that TP53 activation is associated with liver cancer cell apoptosis by regulating the expression of Bcl-2 and caspases ( 41 , 42 ), in addition to inhibiting cancer cell migration ( 43-45 ). TP53 activation has also been previously reported to serve an inhibitory role in the EMT process, in human oral mucosal fibroblasts and oral submucous fibrosis by downregulating N-cadherin expression ( 46 ) and in colorectal cancer cells by downregulating Snail expression ( 37 ), which are findings consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…EMT was also notably suppressed, as demonstrated by the downregulation of N-cadherin, snail and twist expression, which are well documented markers of EMT (37,38). (41,42), in addition to inhibiting cancer cell migration (43)(44)(45). TP53 activation has also been previously reported to serve an inhibitory role in the EMT process, in human oral mucosal fibroblasts and oral submucous fibrosis by downregulating N-cadherin expression (46) and in colorectal cancer cells by downregulating Snail expression (37), which are findings consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Tumor protein p53 induces cell cycle arrest and apoptosis through the transcriptional regulation of BAX gene. The protein also upregulates Bak expression, and the activation of Bax and Bak induces activation of caspase-3 [31]. In HepG2 cells, we have found that R2-viniferin tended to arrest cell cycle at G2/M phase, increased intracellular ROS levels, and the Bax/Bcl2 ratio in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 79%
“…It has been previously reported that TNBS-induced colitis is associated with apoptosis of the colonic epithelial cells and its toxicology is thought to be related to the induction of apoptosis and the destruction of the intestinal mucosal barrier [24,25]. In IBD, there are high levels of apoptosis in the intestinal epithelium of patients [26,27]. The increased number of apoptotic epithelial cells and elevated Bax but attenuated Bcl-2 during active colitis may lead to a defective epithelial barrier and result in pathogenic microorganism in ltration.…”
Section: Anemoside B4 Suppressed Tnbs-induced Proliferation and Apoptmentioning
confidence: 99%